1998
DOI: 10.1073/pnas.95.23.13687
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid alters the intracellular trafficking of the mannose-6-phosphate/insulin-like growth factor II receptor and lysosomal enzymes

Abstract: Previously, we showed that retinoic acid (RA) binds to the mannose-6-phosphate͞insulin-like growth factor II receptor (M6P͞IGF2R) with high affinity, suggesting that M6P͞IGF2R may be a receptor for RA. Here, we show that RA, after 2-3 h of incubation with cultured neonatal-rat cardiac fibroblasts, dramatically alters the intracellular distribution of M6P͞IGF2R as well as that of cathepsin B (a lysosomal protease bearing M6P). Immunof luorescence techniques indicate that this change in intracellular distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…In contrast, receptor down-regulation in choriocarcinoma cells by antisense M6P/IGF2R RNA increases both tumor cell growth rate and tumorigenicity (O'Gorman et al, 1999). The M6P/IGF2R also contains a retinoic acid (RA) bind site (Kang et al, 1997), and receptor overexpression in RA-resistant cancer cells lacking functional RA nuclear receptors confers susceptibility to RA-induced apoptosis (Kang et al, 1999). The results of these functional studies, coupled with frequent M6P/IGF2R mutation in a number of human cancers, demonstrate the importance of this genetic target in human carcinogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, receptor down-regulation in choriocarcinoma cells by antisense M6P/IGF2R RNA increases both tumor cell growth rate and tumorigenicity (O'Gorman et al, 1999). The M6P/IGF2R also contains a retinoic acid (RA) bind site (Kang et al, 1997), and receptor overexpression in RA-resistant cancer cells lacking functional RA nuclear receptors confers susceptibility to RA-induced apoptosis (Kang et al, 1999). The results of these functional studies, coupled with frequent M6P/IGF2R mutation in a number of human cancers, demonstrate the importance of this genetic target in human carcinogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence to date suggests, however, that the M6P/ IGF2R is not involved in cell signaling (Korner et al, 1995); this function is mediated primarily by the insulin-like growth factor I receptor (IGFIR) and the insulin receptor isoform A (Czech et al, 1989;Frasca et al, 1999). The M6P/IGF2R has also been shown to be mutated in a number of human cancers, including those that develop in the liver, breast and colon (Jirtle et al, 1999b), and to suppress cancer cell growth (Kang et al, 1999;O'Gorman et al, 1999;Souza et al, 1999). These ®ndings are consistent with the M6P/ IGF2R functioning normally as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…Since the M6P/IGF2R is well characterized as a trafficking receptor whose activities include intracellular transport to lysosomes, localization of proteins at the cell surface, and internalization of extracellular ligands (Kang et al, 1998;Blanchard et al, 1999;Godar et al, 1999;Jadot et al, 1999), we investigated the possibility that the M6P/IGF2R might be important for CREG localization. Previous immunofluorescence studies of transiently transfected CREG showed predominant staining of overexpressed CREG in the ER and Golgi (Veal et al, 2000).…”
Section: M6p/igf2r Regulates Endogenous Creg Localizationmentioning
confidence: 99%
“…TTNPB is an agonist of ATRA, which binds to the RAR nuclear receptor, but not the M6P/IGF-2 receptor at the host cell surface, and thus, can be used to differentiate effects of ATRA that result from binding to the M6P/IGF2 receptor or RAR receptor (12). Therefore, these results indicated that ATRA inhibited binding of C. pneumoniae to the M6P/IGF2 receptor [8].…”
Section: Pretreatment Of Host Cells With Retinoic Acid and Ttnpb Inhimentioning
confidence: 99%
“…Binding of ATRA to the cellular M6P/IGF2 receptor affects binding of the phosphomannosylated residues and alters intracellular trafficking of the M6P/IGF2 receptor and its ligands [12]. In addition, ATRA has anti-oxidant properties and can elicit a variety of cellular responses affecting cell growth, differentiation, and metabolism [13,14] and interfere with glycosylation of viral proteins [15].…”
Section: Introductionmentioning
confidence: 99%